Philosophy of Science and Scientific Ethics as the Foundation of Professionalism for Primary Madrasah Teachers in the Digital Age - Nurmala, Umi Ivayatuz Zulva; Aulia, Putri; Irmawati, Waryunah; Muwafiqi, Muhammad Zukhruf (Bidayatuna Jurnal Pendidikan Guru Mandrasah Ibtidaiyah, 2025)
Digital transformation has fundamentally reshaped teacher professionalism, requiring capacities that extend beyond technical pedagogy toward epistemological and ethical competencies. This study aims to conceptualize Madrasah Ibtidaiyah (MI) teacher professionalism in the digital era through the integration of philosophy of science, scientific ethics, and digital competence. Using a qualitative descriptive library research design, 23 peer-reviewed journal articles were systematically selected from international open-access databases, with a preference for Scopus-indexed sources. Data were analyzed through thematic and qualitative content analysis. The findings indicate that MI teacher professionalism is a multidimensional construct shaped by four interrelated dimensions: epistemological awareness, scientific and Islamic ethics, digital competence, and structural–systemic conditions. Epistemological understanding enables teachers to critically evaluate digital knowledge and mitigate misinformation, while scientific ethics provide moral integrity and responsibility in digitally mediated pedagogy. Digital competence functions as the enactment of epistemological and ethical orientations in practice, whereas institutional structures determine the sustainability of professional enactment. This study contributes to international scholarship by proposing an integrative, value-oriented framework of teacher professionalism relevant to faith-based and comparative education systems confronting digitalization.